Potent ex vivo activity of naphthoquine and methylene blue against drug-resistant clinical isolates of Plasmodium falciparum and Plasmodium vivax - Wirjanata, G; Sebayang, BF; Chalfein, F; Prayoga; Handayuni, I; Trianty, L; Kenangalem, E; Noviyanti, R; Campo, B; Poespoprodjo, J; Möhrle, JJ; Price, R; et al. (American Society for Microbiology, 2015)
The 4-aminoquinoline naphthoquine (NQ) and the thiazine dye methylene blue (MB) have potent in vitro efficacies against Plasmodium falciparum, but susceptibility data for P. vivax are limited. The species- and stage-specific ex vivo activities of NQ and MB were assessed using a modified schizont maturation assay on clinical field isolates from Papua, Indonesia, where multidrug-resistant P. falciparum and P. vivax are prevalent. Both compounds were highly active against P. falciparum (median [range] 50% inhibitory concentration [IC50]: NQ, 8.0 nM [2.6 to 71.8 nM]; and MB, 1.6 nM [0.2 to 7.0 nM]) and P. vivax (NQ, 7.8 nM [1.5 to 34.2 nM]; and MB, 1.2 nM [0.4 to 4.3 nM]). Stage-specific drug susceptibility assays revealed significantly greater IC50s in parasites exposed at the trophozoite stage than at the ring stage for NQ in P. falciparum (26.5 versus 5.1 nM, P = 0.021) and P. vivax (341.6 versus 6.5 nM, P = 0.021) and for MB in P. vivax (10.1 versus 1.6 nM, P = 0.010). The excellent ex vivo activities of NQ and MB against both P. falciparum and P. vivax highlight their potential utility for the treatment of multidrug-resistant malaria in areas where both species are endemic.